Pengaruh Penggunaan e-Modul Materi Senyawa Hidrokarbon dalam Pembelajaran Mandiri Kelas XI di SMA Negeri 3 Palangka RayaTahun Pelajaran 2020/2021 - Kartikasari, Santi; Abudarin, Abudarin; Hadjranul Fatah, Abdul (Jurnal Riset Pendidikan Kimia (JRPK), 2021)
This study aims to (1) determine and describe the effect of the use of the e~Module of hydrocarbon compounds on the independent learning outcomes of class XI students of SMA Negeri 3 Palangka Raya, and (2) describe the student's response to the use of the e~Module of hydrocarbon compounds on student self-study outcomes. class XI SMA Negeri 3 Palangka Raya. This research is a quasi-experimental study, the sample of this research is 60 students, namely students in class XI~MIPA 1 and XI~MIPA 2 odd semesters for the academic year 2020/2021. This study uses a Posttest-Only Control Design. At the end of the lesson, the two sample classes were given a cognitive test using the same instrument and tested qualitatively and quantitatively. Data was collected by using multiple choice test method with five options. The test method was carried out to obtain the final score data after being treated in the quasi-experimental group and the control group. The hypothesis was tested using a t-test and was preceded by a prerequisite test which included a normality test and a homogeneity test, the student's response to the use of the e-module was quantified and the percentage calculated. The results showed that there was an effect of using e~Modul on the mastery of the concept of hydrocarbon compounds in SMA Negeri 3 Palangka Raya students with a significance level of 5% (thit 5.19 greater than the value of ttab = 2.05). The results of the student response analysis showed a positive response with an average value of 95.67%, which means that the e~Modul helps class XI students of SMA Negeri 3 Palangka Raya in understanding the concept of hydrocarbon compounds independently. Keywords: e~Module of hydrocarbon compounds, independent study, learning outcomes.